A flexible dual‐mode dual‐port wearable antenna with low‐profile and wideband. Issue 12 (20th November 2022) - Gao, Guo‐Ping; Yu, Zhuo‐Qi; Dong, Jing‐Hang; Hu, Bin
Abstract: A low‐profile wideband dual‐mode (on‐/off‐body mode) dual‐port wearable antenna with flexible substrate is presented for the 5 GHz wireless body area network (WBAN) communications. Using polydimethylsiloxane (PDMS) and felt as substrate, the proposed antenna has a compact structure and is easy to manufacture. In particular, the on‐body mode is realized by the circular patch loaded with a concentric ring on the lower substrate, and the off‐body mode is realized by a rectangular patch with two asymmetric slots etched on the upper substrate. The prototype is fabricated and a good performance is realized with a measured fractional bandwidth of 14.2%, a mutual coupling below −22 dB, a peak gain of 6.59 dBi for on‐body mode and 8.84 dBi for off‐body mode, as well as an envelope correlation coefficient smaller than 0.001. In addition, the antenna exhibits a robust performance near human tissue and low specific absorption rate values. These properties make the proposed antenna a well candidate for wearable systems.